Athena in the World of Techne: The Gender Dimension of Technology, Innovation and Entrepreneurship - Ranga,Marina (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2010)
Long confined to the realm of feminist studies, issues pertaining to womens access, participation, advancement and reward are rising to prominence in innovation, technology and entrepreneurship -areas traditionally characterised either by gender-blindness or male dominance. The implications of this shift are wide-ranging but the mechanisms by which it takes place are little known. We discuss causes of the relatively small numbers of women scientists, researchers, innovators or entrepreneurs, the exceedingly slow pace of transition from inequality to equality and the usually lower hierarchical positions than mens in academia or business, womens hidden roles in technological change and an exemplary instance of womens leading role in a major technological innovation with wide social impact, in the context of major changes arising in the transition from the Industrial to the Knowledge Society.